The effect of ultrasonic irradiation on the microstructure and corrosion rate of a Zn–4.8wt.% Al galvanising alloy used in high performance construction coatings - James Sullivan (Surface and Coatings Technology, 2016)
The microstructure and corrosion resistance of a Zn–4.8 wt.% Al alloy, typically used for high performance galvanised coatings for construction, was modified by the application of ultrasound during solidification. The alloy exposed to ultrasound had an increased volume fraction of smaller, discrete primary η Zn phase regions that were more uniformly distributed throughout the casting. The morphology of η Zn was altered from dendritic to globular and the Zn/Al eutectic growth was disrupted in localised areas from lamellar to anomalous. These changes were likely due to the physical action of the ultrasound disrupting compositional effects, fragmenting dendrites and through the development of cavitation events causing disruptive mixing. These microstructural changes produced an enhanced cut-edge corrosion resistance of the alloy in 0.1% NaCl when coupled with steel mimicking in service coating conditions that was investigated using the SVET. The primary η Zn crystal regions were focussed sites for anodic Zn dissolution and the smaller η regions produced by ultrasound reduced the corrosion rate by preventing the development of crevice like phenomena that may be associated with larger dendrites. The number and size of primary η Zn regions affected the corrosion rate with reductions in these factors reducing the corrosion rate of the alloy.